Caenorhabditis elegans saposin-like spp-9 is involved in specific innate immune responses - Madhu, Bhoomi (Genes Immun, 2020)
Animals counter specific environmental challenges with a combination of broad and tailored host responses. One protein family enlisted in the innate immune response includes the saposin-like antimicrobial proteins. We investigated the expression of a Caenorhabditis elegans saposin-like gene, spp-9, in response to different stresses. spp-9 expression was detected in the intestine and six amphid neurons, including AWB and AWC. spp-9 expression is increased in response to starvation stress. In addition, we discovered pathogen-specific regulation of spp-9 that was not clearly demarcated by Gram nature of the bacterial challenge. Multiple molecular innate immune response pathways, including DBL-1/TGF-β-like, insulin-like, and p38/MAPK, regulate expression of spp-9. Our results suggest spp-9 is involved in targeted responses to a variety of abiotic and bacterial challenges that are coordinated by multiple signaling pathways.